The Effects of Medium Chain Fatty Acids in Mash and Crumbled Pellet Diets on Growth Performance of Broilers - Gage E. Nichols; Haley K. Wecker; Caitlin E. Evans; Cassandra K. Jones; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this experiment was to determine the effects of medium chain fatty acids (MCFA) in mash and crumbled pellet broiler diets. A total of 400 male chicks (Cobb 500; initial BW 0.092 lb) were housed in 4 Petersime batteries and used in an 18-d study. Treatments were randomly assigned to 80 cages within location block resulting in 8 cages per treatment with 5 chicks per cage at placement. Treatments were arranged in a 2 × 5 factorial with main effects of feed type (mash and crumbled pellet) and 0.5% MCFA inclusion (no inclusion, control; hexanoic acid, C6; octanoic acid, C8; decanoic acid, C10; and dodecanoic acid, C12). Fat inclusions in the diets were equalized using 0.5% soybean oil in the control diet. Prior to crumbling, diets were conditioned at 185°F for approximately 20 s and pelleted (CPM, model CL-5, Crawfordsville, IN) with a 5/32 × 7/8 in. ring die. Dietary treatments were fed for the full duration of the study. There was no evidence of feed form × MCFA interactions. From d 0 to 18, chicks fed pelleted diets had improved (P<0.001) body weight gain (BWG), feed intake (FI), feed conversion ratio (FCR), and final BW compared to those fed mash diets. For the overall treatment period, there was no evidence of a MCFA effect (P>0.10) on broiler performance. Pelleting and crumbling feed improved growth performance regardless of MCFA inclusion. The MCFA inclusion did not positively influence growth performance of broilers.
Keywords: broilers; medium chain fatty acids; pellet; poultry